Development of Maluku Culture-Based Mathematics Learning Video "Saureka-Reka Dance" Using Powtoon - Lapele, Dina Amalya; Nurur, Zumrotin; Buton, Iskandar; Umagapi, Nur Afni (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Maluku is one of the provinces in Eastern Indonesia which has a variety of cultures. Various Maluku cultures contain mathematical values that we can use as a learning approach. Maluku culture, such as the shape of traditional houses, maritime activities of the Maluku people, and traditional Maluku dances contain mathematical values that we can explore in learning mathematics. This culturally integrated mathematics learning will help students understand concepts because the material studied is related to students' lives. This research used Research and Development method that aims to develop a mathematics learning video based on Maluku culture, namely the Saureke-Reka dance using Powtoon. This research used ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. The learning videos discusses the learning of Mathematics contained in the "Saureka-Reka" dance. The reason for choosing the object of dance study is because the "Saureka-Reka" dance is a dance that is popular among young people in Maluku, from elementary school to university level. This dance is also often used as an everyday game. This media is made with the integration of culture, mathematics, and of course technology. Data collection techniques in this study was a questionnaire. The data collection instruments used were material expert and media expert validation instruments, and questionnaire sheets. Data were analyzed using descriptive quantitative techniques. This study uses the ADDIE model (Analyze, Design, Develop, Implementation, Evaluation). The results of the study show that the learning videos developed are declared very feasible. It can be seen from the value of the validity test by material experts is 84% and the value of the validity test by media experts is 86%. The practicality test results by users reach a value of 90% which indicates that this media is very practical. Media users responded positively to this media. Some positive responses include that this media is interesting and helps them understand the material. Thus, researchers highly recommend this media for use in mathematics learning. This media is passive or one-way only. The author recommends that future researchers can develop more interactive media.